Hypolipidemic and cardioprotective effects of Ulva lactuca ethanolic extract in hypercholesterolemic mice. (8th August 2018) - Kammoun, Intissar; Ben Salah, Hichem; Ben Saad, Hajer; Cherif, Boutheina; Droguet, Mickaël; Magné, Christian; Kallel, Choumous; Boudawara, Ons; Hakim, Ahmed; Gharsallah, Neji; Ben Amara, Ibtissem
Abstract: Context: Hypercholesterolemia has significant cardiac consequences, since it is among the major risk factors of ischemic heart diseases. Objective: The aim was searching the cardioprotective effect of chemical constituents from the sea lettuce Ulva lactuca upon hypercholesterolemic regime in mice. Material and methods: Mice were randomly divided into three groups: untreated group, hypercholesterolemic group, and mice receiving 1% cholesterol associated with U. lactuca ethanolic extract. Results: In vitro study demonstrated that algal extract has antioxidant efficacy attributable to the presence of phenolic compounds. Additionally, the alga alleviated cardiotoxicity, as shown by the improvement of haematological parameters, white cell viability, heart oxidative stress, plasma biochemical parameters and index of atherogenesis. Gene expression of the proinflammatory cytokines TNF-α, IL-1β and IL-6 significantly decreased in the heart of U. lactuca supplemented hypercholesterolemic animals. Conclusion: It was established that the green alga, thanks to its bioactive compounds, effectively counteracts cardiotoxic effects of hypercholesterolemic regime.